Penerapan Kombinasi Teori Belajar Pavlov dengan Teori Belajar Kognitif Untuk Meningkatkan Hasil Belajar Matematika pada Siswa SMA Negeri 1 Indra Makmur - Setiawan, Heri (Jurnal Riset Ilmu Pendidikan, 2022)
The purpose of this research is to find out whether by applying the combination of Pavlov's x-learning theory with cognitive learning theory can improve students' mathematics learning outcomes on the subject of a two-variable linear inequality system discussion at SMA Negeri 1 Indra Makmu and to find out how active students are in the learning process. The population of this research is all class X Science1. Student improvement data obtained in the field is written in tabular form. The table shows a very good increase in learning outcomes, so it can be concluded that by using the application of a combination of Pavlovh's theory of learning with cognitive learning on the subject of a two-variable linear inequality system, there is an increase in learning outcomes in class X Science 1 at SMA Negeri 1 Indra Makmur